Peran Ai-Diven Personalisasi Rekomendasi Konten dan Kepuasan Pengguna dalam Meningkatkan Engagennt Pengguna Netflix - Al- Hafiz, Zidan Akbar; Rully, Tutus; Hikam, Ahmad Badru; Kamil, M Ihsan; Putra, Muhammad Denis Pratama; Pratama, Lanang Galih; Ar-Rasyid, Muhammad Fattah; Andriyansyah, Andriyansyah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
The rapid development of Artificial Intelligence (AI) has transformed digital marketing strategies, particularly through the implementation of AI-driven personalization in streaming service platforms. Netflix is one of the leading platforms that utilizes AI-based recommendation systems to deliver content tailored to users’ preferences. This study aims to examine the effect of AI-driven personalization on Netflix user engagement, with user satisfaction acting as a mediating variable. A quantitative research approach was employed, with data collected through questionnaires distributed to Netflix users. The data were analyzed using multiple linear regression analysis, supported by validity, reliability, and classical assumption tests. The results indicate that AI-driven personalization has a significant positive effect on user engagement. Furthermore, user satisfaction also shows a positive influence and plays a mediating role in strengthening the relationship between AI-driven personalization and user engagement. These findings suggest that relevant, accurate, and user-friendly content recommendations enhance user satisfaction and foster sustained user engagement. This study provides theoretical contributions to AI-based digital marketing literature and practical implications for Netflix in optimizing personalization strategies to improve user loyalty and engagement in the era of Marketing 6.0.